Application of next-generation sequencing for the high-resolution typing of MHC-B in Korean native chicken - Ediriweera, Thisarani Kalhari; Manjula, Prabuddha; Cho, Eunjin; Kim, Minjun; Lee, Jun Heon (Frontiers in Genetics, 2022)
The major histocompatibility complex-B (MHC-B) region of chicken is crucially important in their immunogenesis and highly diverse among different breeds, lines, and even populations. Because it determines the resistance/susceptibility to numerous infectious diseases, it is important to analyze this genomic region, particularly classical class I and II genes, to determine the variation and diversity that ultimately affect antigen presentation. This study investigated five lines of indigenous Korean native chicken (KNC) and the Ogye breed using next-generation sequencing (NGS) data with a Geneious Prime-based assembly and variant calling with the Genome Analysis Toolkit (GATK) best practices pipeline. The consensus sequences of MHC-B (BG1-BF2) were obtained for each chicken line/breed and their variants were analyzed. All of the KNC lines possessed an excessive number of variants, including an ample amount of high-impact variants that provided useful information regarding modified MHC molecules. The study confirmed that NGS techniques can effectively be used to detect MHC variabilities and the KNC lines are highly diverse for the MHC-B region, suggesting a substantial divergence from red junglefowl.